Biomechanical analysis of fundamental human movements - Chapman, Arthur E., ....- (Champaign : Human Kinetics, 2008)
This is an advanced biomechanics text using mechanical, mathematical and biological definitions and concepts and the application to human movements. It provides a brief but explicit introduction to the elements of biomechanical analyses and the principles that underlie all human motion and then delves into a complete array of fundamental human movements and their components. Readers are led through a progression of logical biomechanical indices that help to identify and build on mechanical and mathematical concepts that explain how human movements are achieved and can be modified.The unique approach of this book is the focus on fundamental human activities as the area within which to develop advanced analytical skills. The author shows how to perform analyses using examples that move from the simple to complex.Superbly illustrated, this book will be invaluable to those pursuing studies in advanced quantitative biomechanics.